Pratylenchus jaehni sp n. from citrus in Brazil and its relationship with P-coffeae and P-loosi (Nematoda : Pratylenchidae) - Inserra, R. N.; Duncan, L. W.; Troccoli, A.; Dunn, D.; dos Santos, J. M.; Kaplan, D.; Vovlas, N. (Brill Academic Publishers, 2001)
A lesion nematode population infecting citrus in the state of São Paulo, Brazil is described and named Pratylenchus jaehni sp. n. Biological, molecular and morphological characteristics of this new species are compared with those of the morphologically similar P. coffeae and P. loosi. Results of mating experiments showed that R jaehni is reproductively isolated from P coffeae. Molecular (D2/D3 DNA sequences) dissimilarities among P. jaehni sp, n., P. coffeae and P. loosi were documented in a previous study. The morphology of seven R coffeae populations from tropical America and eastern Java and a P loosi population from Sri Lanka is used for comparison with the morphology of P. jaehni sp. n. Pratylenchus jaehni differs from R coffeae and P. loosi by only a few morphological ;characters of the females. The mean values of stylet length, stylet knob height, and vulva position are smaller (less than or equal to15 vs greater than or equal to15 mum, less than or equal to2.7 vs greater than or equal to2.7 mum, less than or equal to79 vs greater than or equal to79%) than those in P coffeae and P loosi. The tail terminus is usually subhemispherical and smooth in P jaehni sp. n.. whereas it is commonly truncate and indented in most P. coffeae populations and bluntly or finely pointed in P. loosi. Because of the morphological similarities among P. jaehni sp. n., P. coffeae and P. loosi, examination of at least ten specimens is required to obtain a reliable diagnosis based on morphology. Nineteen morphometric parameters for P. jaehni sp. n. and P. coffeae ranged from 0-13% smaller in fixed than in live specimens.
Keywords: lesion nematode; mating; taxonomy